2000
DOI: 10.1097/00004728-200001000-00028
|View full text |Cite
|
Sign up to set email alerts
|

MR Observations of Posttraumatic Osteolysis of the Distal Clavicle After Traumatic Separation of the Acromioclavicular Joint

Abstract: The MR features of posttraumatic osteolysis are characteristic of this process. We advocate the use of MRI in patients with chronic AC joint pain who have had a prior AC joint dislocation, particularly if follow-up radiographs are nonspecific, equivocal, or do not indicate the presence of secondary osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Osteolysis of the lateral clavicle may be related to disorders in the microenvironment of the distal clavicle, but the specific mechanism is not known. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Osteolysis of the lateral clavicle may be related to disorders in the microenvironment of the distal clavicle, but the specific mechanism is not known. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of shoulder pain is highest among manual wheelchair users with tetraplegia and paraplegia [2], who use their upper limbs repeatedly each day for wheelchair propulsion and transfers. Studies using ultrasonography [19], physical examination [20,21], and magnetic resonance imaging [22] have shown that the shoulder pain in manual wheelchair users is attributed to various pathologic changes, including rotator cuff tears [7,23], degenerative changes [20,24], impingement [25], and osteolysis [22,26]. Shoulder abnormalities have been linked to propulsion biomechanics [27,28] and muscle imbalances [13,29].…”
Section: Introductionmentioning
confidence: 99%
“…20 However, osteolysis has also been repeatedly described in patients with no radiological pathologies after the injury. Although usually self-limiting within 18 months, post-traumatic osteolysis may lead to irreversible vanishing of the distal 0.5-3 cm of the clavicle.…”
Section: Introductionmentioning
confidence: 99%